Prospects of Youths’ Entrepreneurship in Nigeria - Enendu , Chimaobim Ijeoma (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
Youth entrepreneurial activities have been identified as a tool for attaining economic development. Many developing countries have attributed the development of their economies to the participation of youths in entrepreneurial activities. Youth entrepreneurial activities have been said to be a constant source of income and boost for the nation’s economy. This paper, therefore, aims to identify some challenges that hinder the youths from engaging properly in entrepreneurship whilst also understanding the prospects within this context. The major challenge identified in the paper includes accessibility to proper infrastructure and opportunities while the key to untapping its prospects lie in bringing opportunities to the forefront and making entrepreneurship part of every students’ educational experience Also, some recommendations were provided which could enhance better functioning as prioritization needs to be applied by the government and the youths themselves in all aspects is critical role in promoting youth entrepreneurial activities.